Opportunities for a Clean and Green Pakistan : A Country Environmental Analysis - World Bank (World Bank, Washington, DC, 2019)
This document aims to deepen the understanding of the effects of environmental pollution on health and standards of living in Pakistan. It seeks to assess institutional capacity to facilitate a transition to environmentally sustainable growth, as well as to strengthen dialogue among different stakeholders. The Country Environmental Analysis (CEA) builds on a substantial body of related work. This includes a CEA conducted in 2006, as well as documents addressing environmental management in Sindh, sectoral water resources, forestry and fisheries management, and analyses of climate risks. The CEA recognizes the importance of increasing climate resilience (Pakistan is the fifth most exposed country in the world to climate change) but climate change management is not themain focus. The CEA is written within the context of recent important institutional and political development, including the 18th Amendment of 2010. These changes included a greater focus on devolution. Most environmental oversight functions were decentralized from the federal government to the provincial administrations, and also involve local governments. Four technical areas of analysis, on the health costs of air and water pollution, on decentralization, on environmental management in Khyber Pakhtunkhwa (KP) and on environmental management of industry in Punjab—provide key inputs. The document builds on consultations involving stakeholders from the national and provincial governments, nongovernmental organizations (NGOs), and international cooperation agencies. Although the CEA recognizes the importance of addressing natural resource degradation and air and water pollution in rural areas, recommendations focus on measures to addresspollution in urban areas. The conclusion is that air and water pollution and natural resource degradation continue to impose heavy costs on Pakistan’s citizens and the economy through their impact on health and productivity. A more environmentally sustainable growth path will play a key role in Pakistan’s longer-term development and transformation to an upper-middle income country. Priorities for improved environmental management focus include (a) improving environmental monitoring by environmental protection agencies (EPAs) and local governments; (b) enhancing the devolution of environmental responsibilities for better service delivery; (c) improving coordination among the federal, provincial, and local levels, and among sectors; (d) ‘greening’ future investments, and (e) using the power of public pressure.